Leadership management of village heads based on soft skill development of coastal communities in Indonesia - Novianty Djafri; Sukma Nurilawati Botutihe; Apriyanto A. J. Pauweni; Mardia Bin Smith; Syamsu Qamar Badu (Problems and Perspectives in Management, 2022)
This study aims to map the soft skills of the coastal area community’s potentials through leadership management of the village heads to be innovative to develop the village growth in the coastal area of northern Indonesia. The study relied on a survey with a mixed method. It involved villagers in Bilato District, Gorontalo Regency, Indonesia, as the population and 33 villagers (village heads, village officials, prominent figures, and villagers) as the sample. It was found that village heads’ leadership management in soft skill development of community potentials based on the village innovation system in the coastal area arrives at a good category. Further, this study found that the village heads’ leadership management in managing potential soft skills and characteristics of village communities in coastal areas based on village innovation systems in Bilato District, Gorontalo Regency, Indonesia, was in the good category with a percentage of 71.4%. This percentage is obtained through several indicators, i.e., (1) leadership management with 76.3% (good category); (2) village head strategy with 75.4%; and (3) innovation system with 66.2% (good category). It is expected that it can be further improved through other indicators apart from the grand design and the analysis of village heads’ leadership management model in managing soft skills of potentials and characteristics of the village community in the coastal area based on village innovation systems. Acknowledgment We would like to express our gratitude to the Head of the Faculty, the Dean of the Faculty of Education, Village Head, and District Head, Local and Provincial Government for the implementation of this study.